2016
DOI: 10.1016/j.ijfatigue.2016.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Faceted crack initiation characteristics for high-cycle and very-high-cycle fatigue of a titanium alloy under different stress ratios

Abstract: a b s t r a c tUltrasonic fatigue tests were conducted at the stress ratios of À1, À0.5, À0.1, 0.1 and 0.5 for a Ti-6Al-4V alloy in high-cycle and very-high-cycle fatigue regimes. Experimental results showed that faceted crack initiation was the main failure mode for specimens at the stress ratios of À0.1, 0.1 and 0.5, and multi-site faceted crack initiation was observed at the stress ratios of 0.1 and 0.5. The measurements indicated that the number of facets increased with the increase of stress ratio. Based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 45 publications
4
60
1
Order By: Relevance
“…The similar rough area characteristic at the crack initiation site is often observed in bidomal equiaxed microstructure at R = −1, which was explained based on the numerous cyclic pressing (NCP) model [14]. The probability of rough area at the crack initiation site is decreased with the increase of the stress ratio of −1 [13]. As for TC21 titanium alloy with basketweave of 40 μm, the fracture surfaces are similar to that of the alloy with basketweave of 60 μm.…”
Section: Fatigue Crack Initiation Analysissupporting
confidence: 56%
See 2 more Smart Citations
“…The similar rough area characteristic at the crack initiation site is often observed in bidomal equiaxed microstructure at R = −1, which was explained based on the numerous cyclic pressing (NCP) model [14]. The probability of rough area at the crack initiation site is decreased with the increase of the stress ratio of −1 [13]. As for TC21 titanium alloy with basketweave of 40 μm, the fracture surfaces are similar to that of the alloy with basketweave of 60 μm.…”
Section: Fatigue Crack Initiation Analysissupporting
confidence: 56%
“…As for titanium alloys with a bimodal microstructure, α grain size [6][7][8], grain distribution [9], crystal orientation [10,11], and super grain (grain clusters with similar orientation) [12] are important factors of the fatigue crack initiation for titanium alloys. The mechanism of the fine granular area (FGA) was supposed to be the cleavage of primary α grains, followed by the growth and coalescence of the adjacent facets [5,13,14]. The probabilities of faceted crack initiation increase with the value of the stress ratio R (the ratio of the min stress to the max stress), and the rough area, other than the facets characteristics, were observed at the stress ratio of −1 [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the VHCF properties should be considered as basic data for the design of the actual components. Recently, the VHCF behaviours of different metallic materials have been investigated …”
Section: Introductionmentioning
confidence: 99%
“…However, Morrissey et al reported that the fatigue crack initiation without facet morphology only on the surface of specimens for Ti‐6Al‐4V alloy at VHCF regime. Hence, the crack initiation mechanisms of Ti‐6Al‐4V alloy at VHCF regime are still not clear …”
Section: Introductionmentioning
confidence: 99%